Rodent Hypoxia–Ischemia Models for Cerebral Palsy Research: A Systematic Review - Rumajogee, Prakasham; Bregman, Tatiana; Miller, Steven P.; Yager, Jerome Y.; Fehlings, Michael G. (Frontiers in Neurology, 2016)
Cerebral Palsy (CP) is a complex multifactorial disorder, affecting approximately 2.5-3 per 1000 live term births, and up to 22 per 1000 prematurely born babies. CP results from injury to the developing brain incurred before, during or after birth. The most common form of this condition, spastic CP, is primarily associated with injury to the cerebral cortex and sub-cortical white matter as well as the deep gray matter. The major etiological factors of spastic CP are hypoxia/ischemia, occurring during the last third of pregnancy and around the birth age. In addition, inflammation has been found to be an important factor contributing to brain injury, especially in term infants. Other factors, including genetics, are gaining importance. The classic Rice-Vannucci hypoxia-ischemia model (in which 7-day-old rat pups undergo unilateral ligation of the common carotid artery followed by exposure to 8% oxygen hypoxic air) is a model of neonatal stroke which has greatly contributed to cerebral palsy research. In this model brain damage resembles that observed in severe CP cases. This model, and its numerous adaptations, allows one to finely tune the injury parameters to mimic, and therefore study, many of the pathophysiological processes and conditions observed in human patients. Investigators can recreate the hypoxia/ischemia and inflammation, which cause brain damage and subsequent motor and cognitive deficits. This model further enables the examination of potential approaches to achieve neural repair and regeneration. In the present review, we compare and discuss the advantages, limitations, and the translational value for cerebral palsy research of hypoxia-ischemia models of perinatal brain injury.